2020
DOI: 10.1016/j.agee.2019.106708
|View full text |Cite
|
Sign up to set email alerts
|

Structural simplification compromises the potential of common insectivorous bats to provide biocontrol services against the major olive pest Prays oleae

Abstract: Crop production intensification often leads to the structural simplification of production systems. This structural simplification is expected to have strong impacts on biodiversity and the provisioning of ecosystem services, but information about this topic is scarce. For instance, no information exists for Mediterranean olive (Olea europaea) groves, despite olive farming representing a significant share of the agricultural sector in some European countries. We investigated the impact of in-farm and landscape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 35 publications
5
27
1
1
Order By: Relevance
“…In agreement, Jonsson et al (2015) tested the effect of supplementary floral resources in kale Brassica oleracea L. fields surrounded by a gradient of moderately simple to highly complex landscapes on parasitism rates and abundance of aphids (mostly Brevicoryne brassicae L.) and diamondback moths Plutella xylostella L. and found that fields surrounded by moderately simple landscapes responded better to local management. However, Costa et al (2020) found differences according to the local management, with higher abundances of P. oleae in mid-complex olive orchards than in low or high complex orchards, in farms ranked from high complex (traditional orchards with low inputs of agrochemicals) to low complex (intensive farms with several seasonal agrochemicals sprays for pest control). This result was assumed to be related with the level of agrochemicals use, which would increase along the intensification level.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In agreement, Jonsson et al (2015) tested the effect of supplementary floral resources in kale Brassica oleracea L. fields surrounded by a gradient of moderately simple to highly complex landscapes on parasitism rates and abundance of aphids (mostly Brevicoryne brassicae L.) and diamondback moths Plutella xylostella L. and found that fields surrounded by moderately simple landscapes responded better to local management. However, Costa et al (2020) found differences according to the local management, with higher abundances of P. oleae in mid-complex olive orchards than in low or high complex orchards, in farms ranked from high complex (traditional orchards with low inputs of agrochemicals) to low complex (intensive farms with several seasonal agrochemicals sprays for pest control). This result was assumed to be related with the level of agrochemicals use, which would increase along the intensification level.…”
Section: Discussionmentioning
confidence: 86%
“…Paredes et al (2013b) showed that areas of herbaceous vegetation and areas of woody vegetation within olive groves were correlated with a decrease of P. oleae abundance. Moreover, Costa et al (2020) found that the abundance of P. oleae was negatively correlated with the amount of forest cover surrounding olive groves at a 1000 m scale.…”
Section: Discussionmentioning
confidence: 97%
“…This categorisation was based on structural orchard features, mainly tree density, because they are strongly related to intensification (e.g. Tous et al., 2010) and biodiversity levels (Costa et al., 2020; Morgado et al., 2020), and because direct information on management intensity (e.g. agrochemicals use, mechanisation) could not be obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, variations in ripening phenology and harvest timing across cultivars and locations create a continuous supply of olives (Rey, 1995, 2011), which can be tracked in space and time by frugivorous birds (Tellería & Pérez‐Tris, 2003, Tellería et al., 2005). Intensification may thus bring benefits through increased olive availability in highly productive orchards (Muñoz‐Cobo & Montesino, 2003; Rey et al., 1996), though consequences may also be negative, particularly for non‐frugivorous species, due to structural orchard simplification (Costa et al., 2020; Morgado et al., 2020) and landscape homogenisation reducing the availability of alternative habitats (Santana et al., 2017). Moreover, intensification is associated with specialisation on a few cultivars (Tous et al., 2010), which together with landscape homogenisation through intensive olive farming may reduce temporal continuity in fruit availability (Rey, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hope et al 23 molecularly confirmed and morphologically identified the consumption of caterpillars by gleaning bat M. nattereri . Finally, while there have been several recent studies focused on the ecosystem services provided by bats 10 , 24 26 , none have focused on the consumption of caterpillars causing significant damage to forests.…”
Section: Introductionmentioning
confidence: 99%